2018
DOI: 10.3390/s18082600
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Humidity Response of Gas Sensors for Medical Applications: Use of Spark Discharge Synthesis of Metal Oxide Nanoparticles

Abstract: The application of gas sensors in breath analysis is an important trend in the early diagnostics of different diseases including lung cancer, ulcers, and enteric infection. However, traditional methods of synthesis of metal oxide gas-sensing materials for semiconductor sensors based on wet sol-gel processes give relatively high sensitivity of the gas sensor to changing humidity. The sol-gel process leading to the formation of superficial hydroxyl groups on oxide particles is responsible for the strong response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…Among the existing printing methods, aerosol jet printing is the most promising technology because it allows the formation of functional elements with a minimum lateral size of up to 10 microns [7][8][9] both on flat and curved substrates [10,11]. This technology has been applied for the manufacture of transistors [12], sensors [13][14][15], solar cells [16], microheaters [17], microantennas [18,19] and interconnects [20]. Previous studies of this technology relied mainly on the formation of thin-film microstructures due to the need for the manufacture of planar electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing printing methods, aerosol jet printing is the most promising technology because it allows the formation of functional elements with a minimum lateral size of up to 10 microns [7][8][9] both on flat and curved substrates [10,11]. This technology has been applied for the manufacture of transistors [12], sensors [13][14][15], solar cells [16], microheaters [17], microantennas [18,19] and interconnects [20]. Previous studies of this technology relied mainly on the formation of thin-film microstructures due to the need for the manufacture of planar electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the formation of narrow (about 30 μm) and conductive Pt lines were performed in order to optimize the parameters of nano-ink for AJP process [ 67 , 68 ]. Such lines are in demand as high-temperature and corrosion-resistant elements of various printed sensors [ 47 , 48 , 69 ]. The formation of Pt lines was carried out using the technology of AJP on a heat-resistant alumina substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum is a noble metal with excellent catalytic properties and high chemical stability [ 42 , 43 ]. In printed technologies, platinum is promising for the manufacture of corrosion-resistant current-carrying contacts [ 44 , 45 ], elements of gas [ 46 , 47 ], temperature [ 48 , 49 ] and biological [ 50 , 51 ] sensors. In our experiments, platinum nanoparticles (PtNPs) were synthesized by spark generator during electrical erosion of platinum electrodes in an atmosphere of Ar, N 2 , and air.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of superficial hydroxy groups on the sensor cross-sensitivity to humidity was investigated in detail in [52]. It was shown that the application of tin dioxide materials synthesized by spark discharge and characterized as having a reduced concentration of superficial hydroxy groups resulted in a significantly decreased parasitic humidity response of the sensing material.…”
Section: Resultsmentioning
confidence: 99%